Methods to estimate edible forage in an elephant grass pasture - Cóser, Antônio Carlos (2003)
The objective of this work was to evaluate the efficiency and reliability of methods to estimate edible forage dry matter on an elephant grass pasture (Pennisetum purpureum Schumach.). Visual comparative yield method (VCYM) and hand plucking (HP) were used. Two samplings, one in March 20, and another in April 5, 2001, with one and four observers for HP and VCYM, respectively, were done. Estimates of edible forage dry matter were analysed by linear regression and the average estimates were compared by using F test with a probability level of 1%. There was no difference between the two sampling methods. Both, VCYM and HP were efficient to estimate potentially edible forage in the elephant grass pasture. The observers training is decisive, especially when VCYM is used.